KONSEP IDEAL DIGITAL EVIDENCE CRYPTOCURRENCY DALAM PERBANDINGAN HUKUM DI INDONESIA, JEPANG, DAN AMERIKA SERIKAT - Angelina Agung Putri Zaman; Muhammad Rustamaji (Verstek, 2025)
This article analyzes the legal comparison in proving digital evidence for money laundering crimes through virtual currencies (cryptocurrency) in Indonesia, Japan, and the United States. The purpose of this article is to derive an ideal concept from a comparative study of digital evidence in Japan and the United States that can be applied in Indonesia. This research employs normative legal research with a prescriptive nature. The approaches used in this research are the Conceptual Approach and the Comparative Approach. The legal materials utilized consist of primary and secondary sources, gathered through literature study. The analysis of legal materials in this study employs the deductive syllogism method. The findings indicate the need for reform in Indonesia's legal system to handle cryptocurrency digital evidence by adopting best practices from Japan and the United States.